ANALISIS PENGEMBANGAN KOMPETENSI KARYAWAN DALAM MEMANFAATKAN DIGITAL MARKETING DI TIARA PHOTO DIGITAL - Ali, Amir; Syaifuddin, Dedy Takdir; Hakim, Abdul (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study focuses on analyzing the development of employee competencies at Tiara Photo Digital in utilizing digital marketing. Data collection methods were conducted through in-depth interviews with management, digital marketing staff, and customers, as well as observations of employees' work processes in using digital marketing tools. The research findings indicate that Tiara Photo Digital has successfully enhanced employee competencies in utilizing digital marketing through a series of structured training sessions, self-learning, and project-based learning. This includes strengthening technical and strategic skills in the use of social media, SEO, content marketing, and data analysis. This competency improvement has positively impacted the company's performance, as evidenced by an increase in visitor numbers and customer satisfaction levels. This study provides insights for other companies in similar industries on the importance of investing in the development of employees' digital competencies as part of their digital marketing strategy to achieve competitive advantage.